Rhein, an active metabolite of diacerein, down-regulates the production of pro-matrix metalloproteinases-1, -3, -9 and -13 and up-regulates the production of tissue inhibitor of metalloproteinase-1 in cultured rabbit articular chondrocytes. - Tamura, T; Kosaka, N; Ishiwa, J; Sato, T; Nagase, H; Ito, A (2001)
OBJECTIVE: Diacerein has proved to be effective in the treatment of osteoarthritis (OA). However, the precise action mechanism of diacerein on OA is not yet fully understood. Therefore, we investigated the effects of rhein, an active metabolite of diacerein, on the production of promatrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinase-1 (TIMP-1) in rabbit articular chondrocytes. DESIGN: Confluent rabbit chondrocytes were treated for 24 or 48 h with rhein, naproxen or dexamethasone in the presence of recombinant human IL-1alpha (rhIL-1alpha). ProMMP-9/progelatinase B in the culture medium was monitored by gelatin zymography, and proMMP-1/procollagenase 1, proMMP-3/prostromelysin 1, proMMP-13/procollagenase 3 and TIMP-1 were analysed by Western blot analysis. The steady-state levels of proMMP mRNAs were examined by Northern blot analysis. Total MMPs activity was also determined using FITC-labeled casein. RESULTS: Rhein suppressed the rhIL-1alpha-induced production of proMMPs-1, -3, -9 and -13 in a dose-dependent manner (0.1-30 microM). The suppressed production of proMMPs-1 and -3 was accompanied by a decrease in the steady-state levels of their mRNAs. Interestingly, rhein increased the production of TIMP-1. These observations were further supported by the fact that rhein decreased the apparent total activity of MMPs in the culture medium. CONCLUSION: We have demonstrated that rhein, an active metabolite of diacerein down-regulates the gene-expression and production of proMMPs and up-regulates the TIMP-1 production. The therapeutic effects of diacerein on OA may be due, at least in part, to the chondroprotective effect of rhein, its active metabolite.